Factors of burnout among teachers: a systematic review - Menon, Husna Amirah; Tan, Lee Shee; Ahmad Zaini, Liyana Syifaa; Wan Othman, Wan Norhayati; Zainudin, Zaida Nor; Mohamad Yusop, Yusni; Anuar, Muharram (Human Resources Management Academic Research Society (HRMARS), 2024)
Burnout, characterized by emotional, physical, and mental exhaustion due to prolonged stress, is a significant concern for teachers worldwide. This systematic review aims to explore and synthesize the primary factors affecting burnout among teachers. Following the PRISMA model, we conducted a comprehensive search in databases such as Scopus and Science Direct and reviewed 12 studies across various educational settings, including primary and secondary schools, universities, colleges, and special education setting. Key findings highlight emotional regulation as crucial in mitigating burnout, alongside factors such as perceived well-being, self-efficacy in handling classroom challenges, levels of work engagement, and the supportive or stressful nature of school environments. While studies varied in methodology and focus, the synthesis underscores these factors as consistently influential across different educational contexts. To address the identified challenges, evidence-based recommendations are proposed for policymakers, educators, and school administrators. Strategies include fostering emotional intelligence training for teachers to enhance emotional regulation skills, implementing well-being programs to support mental health, promoting self-efficacy through professional development opportunities, fostering a positive work environment to increase engagement, and tailoring support systems that consider the unique contextual factors of each educational setting. This systematic review provides actionable insights for stakeholders aiming to mitigate teacher burnout and enhance overall well-being within educational settings as well as highlighting the limitations to fill the current literature gap.